Strategy Map Development for the Central Bank of Nepal Using Balanced Scorecard - Shova Niroula; Qingmei Tan; Aswin Parajuli (European Scientific Journal, ESJ, 2021)
This paper focuses on how the development of the strategy map for the Central Bank of Nepal is done by linking the key measures with the four perspectives of Balanced Scorecard perspectives (finance, customer, internal process, and learning and growth). The central bank is a vital part of an economy, and therefore it should not limit its strategy implementation and performance measurement within the financial perspectives only. So, this paper serves the purposes of creating a road map for discovering the key indicators to create the strategy map and to support future research in the Nepalese banking field. In the absence of a previous strategy map, the strategic goals of the bank were derived from the relevant literature, the bank’s vision, mission, goals, and mandates followed by the expert’s selection. A list of the bank’s strategic goals was derived from the survey questionnaire corresponding to the four perspectives of Balanced Scorecard. The measures of perspective were studied by factor analysis. The research therefore uses a descriptive-exploratory method. Finally, the strategy map was developed and the result consisted of the strategic goals and measures in financial, customer, internal process, and learning and growth.